Climate Change Mitigation in Practice: Ecosystem Restoration Around Lake Singkarak, Sumatra - Burgers, Paul (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
An increasing important component of climate change mitigation is restoring degraded lands, while improving the economies of communities living in and around degraded forests. The national Low Emission Development Strategies (LEDS) in Indonesia have put ecosystem restoration and sustainable forest management (including social forestry) in degraded areas upfront. In line with the Indonesian and global climate change policies, a Dutch-based social enterprise named CO2 Operate, has been running a Voluntary Carbon Mechanism (VCM) scheme in West Sumatra’s Singkarak Lake watershed since 2009. The scheme is entirely financed through private sector carbon offsetting. In close collaboration with the Provincial Forestry Department and local partners in education, the VCM scheme brings back tree cover to restore ecosystem functions on the degraded slopes of lake Singkarak. A combination of Assisted Natural Regeneration (ANR) and tree planting brings both significant environmental and livelihood improvements. The ecological and cost effective approach allows for even the poorest farmers to join and improve their livelihoods. It brings back a forested landscape and its associated biodiversity within 5 years, while significant carbon sequestration above and below ground fits the low emission development of the Indonesian government to mitigate climate change.